Մեծ Հայքը Կլավդիոս Պտղոմեոսի «Աշխարհագրության» համակարգում - Միքայել Մալխասյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
“География” Клавдия Птолемея является очень важным источником для исследования административно-территориальной системы Великой Армении в середине II в. н. э.. Claudius Ptolemy’s “Geography” is an important source for the research on the administrative-territorial system of Greater Armenia in the middle of the 2nd century A.D..
Keywords: History; Ancient History; Mathematical geography; Cartography